The Effect of Focusky-Aided Scientific Approach on Learning Motivation and Mathematical Reasoning Ability of Junior High School Students on Square Materials - Putri Amaliyani Damanik; Nurhasanah Siregar (JMEA : Journal of Mathematics Education and Application, 2022)
This study aims to determine whether there is an effect of the scientific approach assisted by focusky on the learning motivation and mathematical reasoning abilities of junior high school students on quadrilateral material. This research is included in the quasi-experimental category. The population in this study were all seventh grade students of SMP Negeri 1 Lubuk Pakam T.A 2021/2022. In this study, two classes were selected as samples, namely class VII-A was selected as the experimental class and class VII-U was selected as the control class through purposive sampling technique, each class consisted of 30 people. The experimental class was given teaching by learning using a scientific approach with help of focusky, while the control class was given teaching by learning using an expository approach. The research instrument used was a learning motivation questionnaire and a test in the form of a description of mathematical reasoning abilities that had been declared valid. The data analysis technique used is the analysis prerequisite test, the average similarity test, the two-group average difference test in pairs and hypothesis testing. Hypothesis testing using independent samples t test and manova test. Based on the result of the hypothesis test of learning motivation, the significance value of 0,008 (0,0080,05) and thitungttabel (2,7642,045) this indicates that there is an effect of the scientific approach assisted by focusky on the learning motivation of junior high school students on quadrilateral material. The result of the hypothesis test of mathematical reasoning ability obtained a significance value of 0,001 (0,0010,05) dan thitungttabel (3,3402,045) this indicates that there is an effect of the scientific approach by focusky on mathematical reasoning ability of junior high school students on quadrilateral material and results of the MANOVA test obtained a significance value of Pillais Trace, Wilks Lambda, Hotelillngs Trace dan Yoys Largets Root of 0,001 (0,0010,05) which means that there is an effect of the scientific approach assisted by focusky on students learning motivation and mathematical reasoning abilities of junior high school students on quadrilateral material.